2015
DOI: 10.1093/gerona/glv152
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Frailty Can Help Emergency Departments Identify Independent Seniors at Risk of Functional Decline After Minor Injuries

Abstract: Measuring frailty in community-dwelling seniors with minor injuries in EDs may enhance current risk screening for functional decline. However, before implementation in usual care, feasibility issues such as inter-rater reliability and acceptability of frailty tools in the EDs have to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…As mentioned previously, even if some biomarkers modulated the relationship between 3-month mobility impairment and ED frailty status, our results indicate that frailty status clearly remains the stronger predictor of mobility impairments in this population. In this regard, these results concur with previous larger studies of the role that frailty measures can have on predicting 3-month postinjury functional or mobility impairments in previously independent injured seniors seen in ED [8,11]. Therefore, our results highlight that ED serum biomarker assays do not add significant predictive values to clinical frailty measures regarding 3-month functional decline or mobility impairments in this population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As mentioned previously, even if some biomarkers modulated the relationship between 3-month mobility impairment and ED frailty status, our results indicate that frailty status clearly remains the stronger predictor of mobility impairments in this population. In this regard, these results concur with previous larger studies of the role that frailty measures can have on predicting 3-month postinjury functional or mobility impairments in previously independent injured seniors seen in ED [8,11]. Therefore, our results highlight that ED serum biomarker assays do not add significant predictive values to clinical frailty measures regarding 3-month functional decline or mobility impairments in this population.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that nearly 15% of previously independent seniors consulting in EDs for a minor injury experience mobility decline six months after the event [6][7][8]. In this injured older population, frailty and its correlates were found to be important risk factors for post-injury mobility decline and functional impairment [3,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The CFS is a 9-point pictorial scale ranging from level 1 (robust) to level 9 (end of life) that is a 2 point extension of the CSHA-CFS [3,13]. The CFS9 has been studied in many settings, but not previously compared to clinical and ultrasound modalities in an ED setting.…”
Section: Clinical Frailty Scalementioning
confidence: 99%
“…Furthermore, little consensus exists on the most accurate frailty assessment instrument among researchers and societies dedicated to geriatric care. A recent study of several emergency departments in Canada suggests modest performance of the Canadian Study of Health and Aging Clinical Frailty Scale (CSHA-CFS), as well as physician overall impression of frailty, for ED patients with AUROCs of 0.637 and 0.667 respectively [13]. However, a comparison of a rapid pictorial based clinical scale with other screening modalities has not yet been performed in the trauma ED setting.…”
Section: Introductionmentioning
confidence: 99%